1993
DOI: 10.1007/bf00231112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of increased serum ferritin levels in patients with hyperthyroidism

Abstract: To further elucidate the mechanism of increased serum ferritin levels in hyperthyroidism, the changes in erythrocytes and serum iron and total iron-binding capacity levels were examined in addition to serum ferritin levels in 13 hyperthyroid patients. The mean values of hemoglobin, red blood cells, and packed cell volume were increased by antithyroid therapy. While the serum levels of iron did not change, those of total iron-binding capacity increased significantly after achieving a euthyroid state. Increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…Presumably, the male group size was too small to achieve similar observations. This is consistent with previous research, where ferritin concentration was increased in hyperthyroid subjects and returned to the normal range after antithyroid therapy (25). The authors suggested that the increase in serum ferritin level in hyperthyroidism may be explained by the direct action of thyroid hormones on its synthesis or accompanying impaired iron utilization.…”
Section: Discussionsupporting
confidence: 91%
“…Presumably, the male group size was too small to achieve similar observations. This is consistent with previous research, where ferritin concentration was increased in hyperthyroid subjects and returned to the normal range after antithyroid therapy (25). The authors suggested that the increase in serum ferritin level in hyperthyroidism may be explained by the direct action of thyroid hormones on its synthesis or accompanying impaired iron utilization.…”
Section: Discussionsupporting
confidence: 91%
“…Several groups have reported that T 3 positively regulates serum ferritin in humans (Macaron & Macaron 1982, Van de Vyver et al 1982, Takamatsu et al 1985, Hashimoto & Matsubara 1989, Kubota et al 1993, Barnum-Huckins & Adrian 2000. Elevated serum ferritin levels were observed in hyperthyroid individuals, and levels decreased significantly after antithyroid treatment which helped to normalize T 3 levels (Macaron & Macaron 1982, Van de Vyver et al 1982, Takamatsu et al 1985, Kubota et al 1993, Barnum-Huckins & Adrian 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum ferritin levels were observed in hyperthyroid individuals, and levels decreased significantly after antithyroid treatment which helped to normalize T 3 levels (Macaron & Macaron 1982, Van de Vyver et al 1982, Takamatsu et al 1985, Kubota et al 1993, Barnum-Huckins & Adrian 2000. Furthermore, administration of T 3 to hypothyroid individuals produced a significant increase in the serum ferritin level (Takamatsu et al 1985, Hashimoto & Matsubara 1989.…”
Section: Discussionmentioning
confidence: 99%
“…SHBG levels are usually elevated in thyrotoxicosis and have been reported to be normal in a few patients with generalized resistance to thyroid hormone (GRTH) [5,6]. Also, a significant body of evidence exists showing a positive correlation between the serum levels of T 3 , T 4 and ferritin [7,8] in patients with abnormal thyroid status. Namely, all of these studies documented elevated serum ferritin levels in patients with hyperthyroidism which normalized when the T 3 and T 4 levels returned to normal.…”
Section: Discussionmentioning
confidence: 99%